2004
DOI: 10.1300/j026v22n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Marketing and Disadvantaged Health Care Segments

Abstract: The purpose of vocational rehabilitation (VR) is to provide disabled individuals with the training and support services needed to assimilate into the workforce. This study incorporates concepts developed in the relationship marketing and internal marketing literature to determine the factors that influence overall satisfaction of vocational training services. Results underscore the importance of social and structural bonds that develop among the multiple stakeholders involved in the VR process. Satisfaction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…In a study in the Yemeni manufacturer-retailer relationship, Mohd Noor, Perumal, and Goaill (2015) found out that social bonds are crucial in affecting retailers' satisfaction. Peltier and Scovotti (2005) sustained that social bond is the most influential factor of satisfaction in the healthcare marketing relationship. Similarly, Gremler, Gwinner, and Brown (2001) found a strong positive relationship between interpersonal bonds and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in the Yemeni manufacturer-retailer relationship, Mohd Noor, Perumal, and Goaill (2015) found out that social bonds are crucial in affecting retailers' satisfaction. Peltier and Scovotti (2005) sustained that social bond is the most influential factor of satisfaction in the healthcare marketing relationship. Similarly, Gremler, Gwinner, and Brown (2001) found a strong positive relationship between interpersonal bonds and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…It seemed that for participants financial necessities had priority over structural and social affairs. While Peltier et al, (2003Peltier et al, ( , 2004 and Pelletier et al, (2007) in their studies showed that social and structural affair were more important than the financial ones. Also, among different internal marketing methods only the informal internal marketing method had a meaningful effect on employees' satisfaction, directly or indirectly.…”
Section: Discussionmentioning
confidence: 93%
“…Peltier, Boyt & Westfall (1997) suggested that loyalty built solely on financial incentives does not provide a sustainable competitive advantage. Although financial compensation is a necessary component of a nurse's job environment, it is by no means a sufficient antecedent to satisfaction and loyalty (Peltier et al 2003(Peltier et al , 2004. Knowledge generation is one of the critical components of achieving a sustainable competitive advantage.…”
Section: Internal Marketing Practices and Employees' Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations